Two new species of Vatica (Dipterocarpaceae) from Peninsular Malaysia - Chua, Lillian Swee-Lian; Thani, Nor-Ezzawanis Abdullah; Yong, Wendy Sze Yee; Mamat, Hamidah (Phytotaxa, 2015)
Two new species of Dipterocarpaceae, Vatica mizaniana and V. abdulrahmaniana are described from Peninsular Malaysia. Vatica mizaniana differs markedly from V. pedicellata, a Bornean endemic, in characters of the leaf and nut. Vatica abdulrahmaniana is differentiated from similar species V. nitens, by its pubescent stellate hairs on young and flowering twigs and semi-persistent floral bracts. The species description is accompanied with illustrations, distribution maps and ecological notes.